2013
DOI: 10.18227/1982-8470ragro.v7i1.760
|View full text |Cite
|
Sign up to set email alerts
|

Adubação potássica em plantas de rúcula: produção e eficiência no uso da água

Abstract: Resumo -A rúcula (Euruca sativa) é uma hortaliça relevante na alimentação humana sendo uma das mais nutritivas, ricas em minerais como potássio, enxofre e ferro, além das vitaminas A e C. Desde o final da década de 90 a rúcula vem conquistando mercado com um aumento na quantidade comercializada e na sua área de plantio. Objetivou-se pelo presente estudo avaliar o efeito de doses de potássio nas características produtivas, leitura SPAD e eficiência no uso da água por plantas de rúcula. O experimento foi realiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
11

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
7
0
11
Order By: Relevance
“…In the present study, although evaluating lettuce, the marketable shoot dry matter was favored by the increase in N doses, which agrees with the result reported by Biscaro et al (2012). Porto et al (2013) evaluated six K 2 O doses (0, 50, 100, 150, 200 and 250 mg dm -3 ) on rocket plants and observed that shoot dry matter production showed a linear response, as a function of K doses, and was favored by K fertilization. In this study, the marketable shoot dry matter benefited from the K supply, which agrees with the result reported by Porto et al (2013) for rocket.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, although evaluating lettuce, the marketable shoot dry matter was favored by the increase in N doses, which agrees with the result reported by Biscaro et al (2012). Porto et al (2013) evaluated six K 2 O doses (0, 50, 100, 150, 200 and 250 mg dm -3 ) on rocket plants and observed that shoot dry matter production showed a linear response, as a function of K doses, and was favored by K fertilization. In this study, the marketable shoot dry matter benefited from the K supply, which agrees with the result reported by Porto et al (2013) for rocket.…”
Section: Resultsmentioning
confidence: 99%
“…The calculations used coriander Kcb values, because of the lack of information on arugula. The initial, intermediate and final Kcb values were 0.15, 1.10 and 0.70, respectively (Silva et al, 2013).…”
Section: Methodsmentioning
confidence: 95%
“…The dose K 2 was adopted according to the recommendation of Porto et al (2013), in a study that points out the maximum water use efficiency by arugula when subjected to this dose, while the dose K 1 was adopted by the authors to study the behavior of arugula in a nutritional condition below the recommended one.…”
Section: Methodsmentioning
confidence: 99%
“…It is one of the most nutritious vegetables, containing minerals such as potassium, sulfur and iron, besides vitamins A and C (Porto et al, 2013). Its cultivation is mainly concentrated among medium and small farmers, which gives it economic and social importance, being a factor of aggregation between man and field (Souza Neta et al, 2013), which makes it a potential crop for cultivation in the semi-arid region.…”
Section: Introductionmentioning
confidence: 99%